Evacuation in case of a nuclear power plant accident - discussion of some ethical questions - Zölzer, Friedo (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2015)
Although the probability of a nuclear power plant accident in the Czech Republic is considered to be extremely low, authorities and citizens have to be prepared. An important part of emergency preparedness is the provision of clear guidelines for the possible evacuation of people from areas of radioactive contamination. In this context, different types of questions need to be addressed: What are the health risks that people remaining in a contaminated area would have to face? When are people to be evacuated, i.e. which radiation levels warrant action? Who is to be evacuated first, i.e. which groups, if any, should take precedence? What are the ethical principles that determine the when and who? This latter question is addressed here. The paper looks at the guidance given by the relevant public documents and identifies a number of ambiguous and contradictory points. It recommends that decision-makers are provided with additional information and are made aware of the ethical aspects of their decisions. It suggests that classical ethical theories such as utilitarianism and deontology can be taken into consideration, but that in an age of globalization a cross-cultural approach may be more appropriate.
Keywords: nuclear power plant accident; emergency preparedness; evacuation; radioactive contamination; ethics; common morality; participatory technology assessment